Jackson Jones and the Mission - Quattlebaum, Mary (Random House, Inc., 2004)
Jackson Jones can't believe the new: the comminuty garden where he's spent months watering, weeding, and waiting for his thorny rosebush to bloom is going to be bulldozed by big city developers. It can't be! Not now that the garden means something to him. Not now that he likes hanging out with the neighbors who tend their own plots...
Keywords: Juvenile Fiction